Determinants affecting customer’s intention to adopt mobile banking in Saudi Arabia - Alsheikh, Layla; Bojei, Jamil (Arab Open University, 2014)
Mobile technologies and services are envisioned as the possible driving force that will create a variety of business opportunities. The objective of the present study is to determine the major factors that contribute towards customer’s intention to adopt mobile banking as electronic-financial services among commercial banks in Saudi Arabia. The research uses primary data and the unit of analysis is individuals who are non-users of mobile banking services. The study questionnaires were distributed to samples throughout Saudi Arabia concentrating on major cities. Four hundred and three valid responses were received and analyzed through multivariate analysis process using Structural Equation Modelling. The study shows that Mobile Phone Experience and Awareness of Service are critical in the comprehension of the technology and its related functionality and benefits while the lack of knowledge and information maximizes the perception of risk. The results also reveal that Performance Expectancy, Effort Expectancy and Perceived Risk are major predictors for adopting mobile banking services in the initial adoption stage. The principal conclusion is that mobile banking services should offer innovative services compared to existing competition services in a similar area, i.e. electronic-banking services. As demonstrated, differentiation can be attained by encompassing more benefit factors than sacrifice factors that create perceived value of adopting mobile banking services in the future.